WHAT TEACHING STRATEGIES MOTIVATE LEARNERS TO SPEAK? - Lestari, Ika Wahyuni (Journal of Foreign Language Teaching and Learning, 2016)
This study aims to investigate learners? perspective on teaching strategies which motivate learners to speak English. Thirty university learners were given questionnaires and one learner was inter- viewed. The 5-point Likert scale questionnaires were interpreted based on ranges of criteria. The interview was used to support or clarify the findings from the questionnaires. This study showed that five teaching strategies: problem-solving strategies, simulation, lecture, role play, and direct con- tact belonged to a strong criterion (mean: 3.00 ? 3.99). It indicated that those strategies motivated learners to speak. In addition, the other five teaching strategies: brainstorming, demonstration, games, large-group discussion, and one-to-one teaching strategies showed the mean score rang- ing from 4.00 to 5.00 which belonged to a very strong criterion indicating that these teaching strategies strongly motivated learners to practice speaking. The current study concluded that the ten teaching strategies motivated learners to speak English; therefore, the use of those teaching strat- egies in teaching speaking skills should be taken into account by teachers and course designers to help learners enhance their speaking skills.